The Manuscript Sermons of Archbishop John Williams - Hampton, Stephen (The journal of ecclesiastical history, 2011)
Most of Archbishop Williams's manuscript remains were destroyed in a fire in 1695. However, the Pepys Library at Magdalene College, Cambridge, contains a volume of manuscript sermons and sermon notes that have not been significantly studied. On closer examination, the sermons can all be dated to the 1640s, and several were delivered on significant occasions. They show that Williams was a far more committed preacher than has generally been acknowledged, and demonstrate his explicit and consistent adherence to Reformed theology. They therefore help in explaining his close links with godly communities and so his significance during the Long Parliament.